Pendugaan Parameter Genetik Ketahanan Tanaman Kakao terhadap Penyakit Busuk Buah - Rubiyo Rubiyo; Sudarsono Sudarsono (Jurnal Tanaman Industri dan Penyegar, 2011)
Rapid method for cocoa breeding as an effort to produce high productivity and quality cocoa clones which are resistant to main disease infected by Phytophtora palmivora, pathogen causing black pod disease, needs to be investigated. For that reason, providing the information about various genetic parameters will really assist to solve the problems in cocoa cultivation and farming in Indonesia. One of the estimation methods of some genetic parameters which is eligible to be used is diallel crossing analysis. The research aimed at estimating genetic parameter of cocoa resistance to the disease caused by P. palmivora, using half dialel crossing. The cross used five cocoa clones as parental clones ( ICCRI 3, TSH 858, DR 1, ICS 13 and Sca 6). The clones represented selected clones resulted from resistance evaluation of previous research, with the resistance level from vulnerable to resistant. The number of genotypes in this research were 15, consisting of 10 F1, and 5 parental clones. Research took place from 2007 to 2008 in Experimental Plot of Kaliwining, Indonesian Coffee and Cocoa Research Center, Jember East Java. Seedlings from the crossing used for the research of every combination consisted of 20 seedlings replicated 3 times. Inoculum type used was mycellia, from selected inoculum in research I. Inoculation was done in leaf and to maintain the moisture (90%) it was covered by plastic. Observation was conducted 3 days after inoculation on the spot area caused by P. palmivora infection. The research indicated that there was no gene interaction in determining resistance to the disease caused by P. palmivora which mostly influenced by additive gene actions. Kd / kr was 1,3594 indicated that there were more dominant gene in parental. Heritability values in a broad and narrow sense belong to high group.